HTLV infection in persons with sexually transmitted diseases in Spain - Ayerdi, Oskar; Benito, Rafael; Ortega, Diego; Aguilera, Antonio; Montiel, Natalia; Pintos, Ilduara; Díaz de Santiago, Alberto; Baza, Begoña; Soriano, Vicente; de Mendoza, Carmen (Frontiers in Immunology, 2023)
Background: HTLV-1 infection is a neglected disease, despite estimates of 10 million people infected worldwide and producing life-threatening illnesses in 10% of carriers. Sexual transmission is the main route of contagion. However, HTLV-1 is not listed among sexually transmitted infections (STI).Methods: Sera from all consecutive individuals attended at six STI clinics across Spain during the last 12 months were tested for HTLV antibodies using a commercial enzyme immunoassay (EIA). Reactive samples were confirmed by immunoblot.Results: A total of 2,524 samples were examined. The majority (1,936; 76.7%) belonged to male, of whom 676 (34.9%) were men who have sex with men receiving HIV pre-exposure prophylaxis. Although native Spaniards predominated (1,470; 58.2%), up to 593 (23.5%) came from Latin America and 139 (5.5%) were Africans.A total of 26 individuals were initially EIA reactive and immunoblot confirmed 5 as HTLV-1 and 7 as HTLV-2. All but one HTLV-1+ came from Latin America. Three were men and two women. Among Latin Americans, the HTLV-1 seroprevalence was 0.67%. In contrast, all seven HTLV-2+ were native Spaniards, formed injection drug users and all but one were HIV+.The rate of HTLV infection among individuals with STI in Spain is 0.5%, greater than in the general population. These results support the introduction of universal HTLV screening in persons attended for STI.